IMPLEMENTASI SISTEM PENUNJANG KEPUTUSAN UNTUK PEMILIHAN EKSTRAKURIKULER MENGGUNAKAN METODE SAW DAN TOPSIS - ardiansyah, syahrul; Desyani, Teti (JATISI, 2025)
Abstract SMK AL-AMANAH is a private vocational high school officially established in the academic year 1996/1997 under the Al Amanah Al Bantani Islamic Boarding School and Education Foundation. Currently, the extracurricular selection process at SMK AL-AMANAH is still carried out manually and does not yet utilize a system that considers students' interests and potential comprehensively. As a result, some students choose extracurricular activities based on peer influence or without considering their personal abilities, which may reduce participation and effectiveness of the activities. This research aims to develop a web-based decision support system to assist students in selecting the most suitable extracurricular activities according to their interests and potential. The system is designed based on criteria determined by the school, such as interest, talent, time availability, and academic performance. The methods used for decision-making are Simple Additive Weighting (SAW) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), both of which are capable of solving multi-criteria decision-making problems objectively. A case study was conducted at SMK AL-AMANAH with system testing using simulated student data. The results of this study indicate that the system can effectively provide extracurricular recommendations and support students in making informed decisions. The system is developed using web programming languages and MySQL as the database. Keywords—Decision Support System, SAW, TOPSIS, Extracurricular, Interest and Potential